Oil Occurrence States in Shale Mixed Inorganic Matter Nanopores - Liang, Shuang; Wang, Jia-Ming; Liu, Yi-Kun; Liu, Bo; Sun, Shuo; Shen, An-Qi; Tao, Fei-Yu (Frontiers in Earth Science, 2022)
In present paper, the mineral and fluid compositions of shale oil from the Songliao Basin are analyzed systematically using core samples, X-ray diffractometer (XRD), and gas chromatography (GC). The effects of shale mineral composition, pore size, temperature, and pressure on the mass density of the adsorbed layers are then studied utilizing molecular dynamics simulation. The results show that illite and quartz are predominant in the micro petrological components of the shale, and nC19 is the main carbon peak. The fluid consists primarily of n-alkane molecules, and nC19 is found to be representative of the shale oil composition. Moreover, the adsorbing effect of quartz-illite mixed wall is between that of a pure mineral wall (illite and quartz), indicating that the selection of a mixed wall is similar to the actual shale composition. If the pores are inorganic, the minimum pore size of only adsorption oil is smaller than the organic pores. The critical adsorption point of shale oil in inorganic pores is less than 3.2 nm. Furthermore, compared to pressure, the temperature has a more significant effect on fluid adsorption due to the correlation with the kinetic energy of alkane molecules. This research shows the oil occurrence status in inorganic matter nanopore with a mixed solid wall, and provides theoretical support for shale oil exploration.